MODEL PENGEMBANGAN KEMITRAAN PENDIDIKAN NON FORMAL DAN INFORMAL DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MEMBERDAYAKAN MASYARAKAT - Lesi Oktiwanti; Adang Danial; H Syaefuddin (Jendela PLS: Jurnal Cendekiawan Ilmiah Pendidikan Luar Sekolah, 2017)
Abstract: This study aims to determine the development of the Partnership Non-Formal Education and Informal Corporate Social Responsibility (CSR) in Empowering Communities conducted in Program "Village Caang" by Creative Institute Collaborate with CSR Chevron Village Mekarjaya District of Sukaresmi, as well as in the village Sarimukti and Karyamekar in District Pasirwangi Garut. Garut. This research uses descriptive method with qualitative approach case study through data collection techniques of interview, observation and documentation on PGPA (Policy, Government and Public Affairs) Chevron CSR; Program manager and field manager of The Creative Institute as Chevron CSR program vendor; and community group beneficiaries Caang Village Program. Based on this research, it is known that The Creative Institute in collaboration with CSR Chevron developed the idea of self-sufficient villages integrated with the name of the village Caang: Caang listrikna which means light of the house with the electrical installation, Caang Otakna which means open society and have the knowledge and skills to meet the needs and empowering lives through the use of natural resources around, Caang Pesakna means people become self-reliant and economically empowered. Keyword: Corporate Social Responsibility, Partnership, Community development, Non Formal and Informal Education.